International Circulations and Inequalities in the Social Sciences: An Introduction - Benz, Pierre; Gautier Morin, Johanna; Klüger, Elisa; Rossier, Thierry (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
This special issue calls for a critical, historically grounded, and interdisciplinary perspective on international circulations and inequalities in the social sciences. It emphasizes the importance of considering the social sciences as a whole and in relation to broader power dynamics. To address inequalities in the production and dissemination of knowledge in the social sciences from diverse perspectives, this special issue brings together scholars from different higher education systems, countries, and disciplines. Its five contributions examine various national contexts, international configurations, and historical periods, utilizing a range of methodological strategies, including document and archival analysis, secondary databases and descriptive statistics, prosopographical databases, and multiple correspondence analysis. The first section of this editorial proposes a socio-historical approach for reflexive study of international circulations and inequalities in the social sciences. The second section situates the five contributions within the transforming context of the internationalization of the social sciences, providing a periodization of these dynamics from the late nineteenth century until the present. Finally, a concluding section advocates for a renewed perspective on the subject.